Victims of environmental violence: a profile of psychosocial damages (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article deals with the issue of environmental violence through the the environmental disaster caused by the ecomafie in Campania, in the so-called  ‘Land of Fires’. The perspective offered by the autors, social psychologists, by highlighting the complex territorial and human phenomenology that this events show aims at enlarging the definition of environmental damage, usually referred to the biomedicalfield, including the damages to the quality of life inflicted on the community.
Keywords: chronical environmental contamination; illegal waste dumping; violence; land of fires; social psychology